Intrinsic Elements in the Novel 7 Deaths by Nahriah Idrus - Ila Nafilah; Reni Rokhayati; Yulia Agustin; Eko Yulianto (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The novel, as a central literary genre, in particular, tells a deep and complex story, recording experiences at various epochs and conveying life's situations and values. And the instinctive demands that every literary work demands from its readers is an analysis of the overall structure of the fictional movement at the time of its narrative. The internal structure of the novel is analyzed using structuralism, which views literary works as integrated structures. Structuralism stipulates that research must focus on the elements and their functional relationships to provide a comprehensive understanding. Its intrinsic elements: subject, plot, characters, setting, language, point of view, and message are the elements that build the work from within. This study aims to: First, identify, describe, and interpret the intrinsic elements in the novel 7 deaths by Nahriah Idrus including: theme, characters and characterization, plot, setting, point of view, style of language, moral message; and Second, analyze the functional relationship between elements. The type of research applied is qualitative research with content analysis method. The results of the study on the intrinsic elements contained in the novel 7 Deaths by Nahriah Idrus, out of a total of 877 intrinsic elements, can be explained that the intrinsic element of setting or setting is the most dominant or numerous element. Therefore, it can be concluded that in the novel 7 Deaths by Nahriah Idrus, many settings or settings are used as intrinsic elements.